Fabrication of zinc doped aluminium oxide/polysulfone mixed matrix membranes for enhanced antifouling property and heavy metal removal. (July 2021) - Sherugar, Prajwal; Naik, Nagaraj S.; Padaki, Mahesh; Nayak, Vignesh; Gangadharan, Athulya; Nadig, Akshatha R.; Déon, Sébastien
Abstract: Heavy metal removal from water resources is essential for environmental protection and the production of safe drinking water. In this direction, Zinc doped Aluminium Oxide (Zn:Al2 O3 ) nanoparticles were incorporated into Polysulfone (PSf) to prepare mixed matrix membranes for the efficient removal of heavy metals from water. These Zn:Al2 O3 nanoparticles prepared by the solution combustion method have a very high surface area (261.44 m 2 /g) with an approximate size of 50 nm. X-ray Photoelectron Spectroscopy analysis showed that the Al and Zn were in +3 and + 2 oxidation states, respectively. Cross-sectional Scanning Electron Microscopy images revealed the finger-like morphology and porous nature of the membranes. In this study, the optimum loading amount of Zn:Al2 O3 nanoparticles was determined. Synthesized membranes showed enhanced hydrophilicity, surface charge, and porosity, which enabled the removal of arsenic and lead with efficiencies of 87% and 98%, respectively. A study of the antifouling properties carried out at various pressures with a feed solution containing Bovine Serum Albumin (BSA) showed 98.4% of flux recovery ratio and reusability up to three continuous cycles. Moreover, this work demonstrates a rational design of novel mixed matrix membranes exhibiting characteristics of hydrophilicity, surface charge, and porosity adequate to realize the efficient removal of heavy metals. Graphical abstract: Image 1 Highlights: Novel Zn:Al2 O3 nanoparticles were synthesized by solution combustion method. Zn reduced hygroscopic nature of Al2 O3 . Novel Zn:Al2 O3 mixed matrix membranes was displayed better selectivity along with good productivity. Mixed matrix membranes exhibited excellent antifouling performance.